2020
DOI: 10.1038/s41598-020-76994-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-hoc analysis of a randomized controlled trial on the impact of pre-transplant use of probiotics on outcomes after liver transplantation

Abstract: Perioperative use of probiotics serves as efficient prophylaxis against postoperative infections after liver transplantation, yet data on long-term effects of pre-transplant probiotic intake is lacking. The aim of this study was to assess the effects of pre-transplant probiotic administration on long-term results of liver transplantation. This was secondary analysis of a randomized trial. Patients were randomized to receive either 4-strain probiotic or placebo before liver transplantation. Five year graft sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Patients have a risk of developing a bacterial infection after liver surgery, which may potentially result in liver failure and even mortality [ 91 ]. Numerous evidence illustrates that the perioperative use of probiotics contributes to lower infection rates and efficient prophylaxis against postoperative infections after liver surgery [ 91 , 92 ].…”
Section: Probiotics and Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients have a risk of developing a bacterial infection after liver surgery, which may potentially result in liver failure and even mortality [ 91 ]. Numerous evidence illustrates that the perioperative use of probiotics contributes to lower infection rates and efficient prophylaxis against postoperative infections after liver surgery [ 91 , 92 ].…”
Section: Probiotics and Liver Transplantationmentioning
confidence: 99%
“…A secondary analysis of a randomized trial showed that the pretransplant administration of 3 × 10 9 colony-forming unit (CFU) probiotic capsules containing Lactococcus lactis PB411 (50.0%), Lactobacillus casei PB121 (25.0%), Lactobacillus acidophilus PB111 (12.5%), and Bifidobacterium bifidum PB211 (12.5%) had benefits on 6-month allograft function, including a decreased international normalized ratio (INR) for prothrombin time, c-reactive protein (CRP) concentration, and AST activity. However, the intake should not be longer than 30 days due to the potential negative effects with the increased levels of INR and γ-glutamyl transferase and abundance of Bacteroides and Enterococcus [ 92 ]. Therefore, probiotics may augment deleterious immune-mediated processes in patients.…”
Section: Probiotics and Liver Transplantationmentioning
confidence: 99%
“…List of compounds identified/isolated from various species of the genus Pistacia. Myrtenol ( 7) Limonene ( 8) Citral (9) α-Phellandrene (10) β-Myrcene (11) Bornyl acetate (12) Terpinen-4-ol ( 13) Myrcene ( 14) p-Mentha-1(7),8-diene (15) Sabinene (16) α-Thujene (17) Camphene (18) p-Cymene (19) cis-Cimene (20) trans-Ocimene (21) β-Phellandrene (22) Limonene dioxide (23) Thymol (24) α-Terpinene (25) α-Terpinolene ( 26) Linalool ( 27)…”
Section: Phytochemistrymentioning
confidence: 99%
“…Among flavonoids, P. atlantica is found to have 5-hydroxy-8-(4-hydroxyphenyl)-7methoxy-2H-2,2-dimethylpyrano-6H-[2,3-g] chromen-6-one (3-methoxy-carpa-chromene) (125) (8), luteolin (126) (9,18,20,23), luteolin-7-glucoside (127) (9), kaempferol (128) (9), naringenin (129) (9,21), naringenin 7-glucoside (130) (9), (+)-catechin (131) (9), rutin (132) (15,21,22,27,28), catechin (133) (21), quercetin (134) (21,22), eriodictyol (135) (23), and apigenin (136) (23).…”
Section: Pistacia Atlanticamentioning
confidence: 99%
“…Another point that makes the comparison between the methodologies of the studies complex is the way of expressing the amount of probiotics administered. Most studies chose to define the amount in CFU (6,8,15,17,18,(21)(22)(23)(24)(25)(26)(27)29,(31)(32)(33)(34). Some works have provided such information in milligrams (1), grams (11), and milliliters (16).…”
Section: Macnaughtan Et Al 2020 (34)mentioning
confidence: 99%